Clinico-Etiological Profile Of Acute Febrile Illness In Children With Sickle Cell Anemia - Tirpude, Bhagyashree; Dr Dipak Madavi; Dr Shamama Subuhi (Innovative Journal of Medical and Health Sciences, 2021)
Objective: In Sickle Cell anemia, fever is a common presenting symptom and is frequently the first indication of serious and life-threatening bacterial infection. Infection is a significant contributor to morbidity and mortality in Sickle Cell anemia. High prevalence of Sickle Cell anemia & lack of study in central India showing causes of fever in them, we studied various causes of fever in patients with Sickle Cell anemia and to provide data which will help to reduce morbidity and mortality by early intervention in patients of Sickle Cell disease. Methods: This was a cross sectional observational study which contains 163 patients of Sickle Cell anemia(SS) presenting with fever in the age group between 6 months to 12 years. All cases were investigated with CBC, blood culture, urine examination, chest x-ray, Blood and Urine Culture and other investigations as indicated. Result: Amongst 163 cases enrolled, most common system to involve was respiratory system(44%), followed by gastrointestinal system(24%) and genitourinary system(8%). In these Pneumonia was the most common clinical diagnosis(23%). Conclusion: We concluded that, the respiratory system was the most common one to get involved in a patients of sickle cell anaemia presenting with fever and pneumonia was the most common diagnosis in it.